2012
DOI: 10.2214/ajr.11.7812
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Associated With Cystic Airspaces

Abstract: At annual repeat CT screening, the finding of an isolated cystic airspace with increased wall thickness should raise the suspicion of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 17 publications
(28 reference statements)
2
89
1
4
Order By: Relevance
“…Although several screening trials have used the maximum diameter of nodules on transverse sections to estimate size, others (iELCAP) have used the average of long-and short-axis diameters measured by using lung windows (4,5,7,14,15). Prediction models used to estimate malignancy yield better results with the average diameter than with the maximum transverse diameter (16).…”
Section: Recommendations For Managing Incidentally Discovered Pulmonamentioning
confidence: 99%
“…Although several screening trials have used the maximum diameter of nodules on transverse sections to estimate size, others (iELCAP) have used the average of long-and short-axis diameters measured by using lung windows (4,5,7,14,15). Prediction models used to estimate malignancy yield better results with the average diameter than with the maximum transverse diameter (16).…”
Section: Recommendations For Managing Incidentally Discovered Pulmonamentioning
confidence: 99%
“…Solid nodules may have external or internal cystic airspace or internal cavitation (15). Subsolid nodules may be either nonsolid or part-solid (7,19,20).…”
Section: Definition Of Nodule Consistencymentioning
confidence: 99%
“…Other findings on the CT scan of the chest should also be reported and these include the presence of discrete cystic airspaces because when the walls of these airspaces show progressive thickening, both in increasing thickness and increasing circumferential wall involvement, these maybe due to lung cancer (15).…”
Section: Other Findings On the Ct Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…Indolent pulmonary cancers comprise ground glass opacities (GGO), solid and cystic nodules, the pathological morphology of which is usually a lepidic pattern, as well as carcinoids and scar adenocarcinomas. Farooqi et al (5) reported a case of a 56-year-old male smoker who had a nodule with a cystic airspace and thin wall in the right lower lobe. The patient was followed up for 33 months, at which time the CT scan showed enlarged solid components and a thickened cyst wall.…”
Section: Introductionmentioning
confidence: 99%